Prevalence and predictors of wound infection in elective clean and clean/contaminated surgery in Khartoum Teaching Hospital, Sudan - Elbur, Abubaker Ibrahim; Yousif, Miraghani; ElSayed, Ahmed; AbdelRahman, Manar (International Journal of Infection Control, 2012)
Background: Surgical site infections are the second most common cause of hospital acquired infections. The objectives of this study were to quantify the rate of wound infection and to identify risk factors associated for its prevalence among patients admitted for elective surgery in Khartoum Teaching Hospital in Sudan. A prospective study was conducted. All patients, aged >18 years admitted during March 1st 2010 to 31th October 2010 were recruited. Baseline data was collected before patient's operations on. Patients were followed up to one month for detection of wound infection using bedside and post-discharge surveillance. A total of 1387 patients were included with a mean age of 35±14 years. 1138(82%) were females. More than three quarters were healthy (79.3%) and 1367(98.6%) patients were operated on conventionally. The total number of the performed surgical procedures was 1426. The rate of wound infection was found to be 9%. Univariate analysis revealed that five variables were significantly associated with the prevalence of wound infection; namely patient’s body mass index (P=0.041), co-morbidity (P=0.006), presence of diabetes (P=0.010), ASA score (P=0.000) and surgical technique (P=0.007). Multivariate logistic analysis showed that ASA score 2 and ASA score > 3, adjusted OR, 1.9 (1.2-3.0), P =0.006 and adjusted OR, 3.6 (2.0-6.7); P<0.001 respectively, laparoscopic surgical technique adjusted OR, 5.5 (2-14.8); P=0.001 were mostly significantly associated with the prevalence of wound infection. The rate of wound infection was high with patient’s physical status and use of the laparoscope technique being strong predictors of infection.